Charismatic Routinization and Problems of Post-Charisma Succession in Kazakhstan, Turkmenistan and Uzbekistan - Isaacs, Rico (Studies of Transition States and Societies, 2015)
Using Weber’s concept of charismatic routinisation, this article analyses the dilemmas related to political succession and post-charismatic order in Kazakhstan, Turkmenistan and Uzbekistan. While the presidents of these three countries have drawn their authority from a combination of charismatic, legal-rational and traditional authority, they have relied most heavily on charisma in particular to sustain their rule. With the presidents of Kazakhstan and Uzbekistan aging and facing the question of political succession, the article provides an analysis of the problems associated with potential for post-charismatic succession in these states. It does so by drawing on three of Weber’s mechanisms for charismatic routinisation: designation, hereditary charisma, and charisma in office. The analysis demonstrates that in these three cases, despite charisma only having two routes available to it, traditional and legal-rational, the mixture of legal-rational, traditional and charismatic domination undermines the process of charismatic routinisation. Consequently, the article argues that political succession in Kazakhstan and Uzbekistan will most likely evolve into a reconstitution of charismatic leadership.